THE POSITIVE IMPACT OF SCHOOL-BASED PEER EDUCATION PROGRAM TOWARDS ADOLESCENT SEXUAL BEHAVIOR: A SYSTEMATIC REVIEW - Pusmaika, Rangga; Novianti, Lidya Latifah (LIFE: International Journal of Health and Life-Sciences, 2017)
The findings of various studies recommend one of the key actions to improve reproductive health is the empowerment of adolescents through educational programs. But there hasn’t been a lot of research that shows this quite clearly. The purpose of this review is to positively impact school-based peer education program for adolescent sexual behavior. The method used is the search through databases such as ProQuest, Scopus, through from SpringerLink, ScinceDirect, and JSTOR using keywords. From the results of screening, 7 studies that meet the criteria has been found. The results of the majority review showed that school-based peer education program towards teenagers sexual behavior has showed positive impact. However, although the uniformity of design study has been applied, the number of samples and duration of intervention allows the occurrence of differences result from the study.